“I could do almost nothing without digital technology”: a qualitative exploration of adolescents’ perception of the risks and challenges of digital technology - Bitto Urbanova, Laura; Madarasova Geckova, Andrea; Dankulincova Veselska, Zuzana; Capikova, Silvia; Holubcikova, Jana; van Dijk, Jitse P.; Reijneveld, Sijmen A. (Frontiers in Psychology, 2023)
The fast development of digital technology and of its use at even younger ages is significantly shaping the current generation of adolescents. This is leading to an almost unlimited accessibility that provides a large number of opportunities, but also to many challenges that adolescents have to face. The aim of our study was to explore the perceptions adolescents have of the risks of digital technology.We conducted online semi-structured interviews as a part of the international Health Behaviour in School-aged Children study. The sample consisted of 15 Slovak adolescents (mean age: 15.33; 20% boys). To analyse our data, we used consensual qualitative research and thematic analysis.Findings: Our findings confirmed that adolescents are aware of the risks associated with the use of digital technology. Regarding their specific types of the perceived risks, we identified four main themes: 1. dependence on the functionality of technology; 2. problematic control; 3. vulnerability in the virtual environment; 4. health risks. Adolescents thus want technology that is functional, safe and does not endanger their health.Despite the fact that adolescents know of the risks they may experience due the digital technology, they still use it. Preventive strategies should focus on functionality, safety and healthiness; furthermore, they should support the constant development of adolescents' digital awareness and raising their awareness about effective and non-threating use of technology.